PEMBERDAYAAN MASYARAKAT KELOMPOK NELAYAN UNTUK MENINGKATKAN PRODUKTIVITASNYA PASCA TERDAMPAK PANDEMI COVID-19 - N.L.N.S Malini; N.K. Arismayanti; I.K.N. Sulibra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This community service activity was carried out in Denpasar City, especially in the Sanur and Pemogan areas. Activities in the form of marine processing packaging training and product promotion; packaging of processed mangrove products; ecotourism development training; and English training. The target groups for this activity are the Segara Agung Sanur Fishermen Group, the Pemogan Batu Lumbang Segara Guna Fisherman Group, the Mina Lestari Batu Lumbang Processing and Marketing Group (Poklahsar) and the younger generation who are the sons and daughters of fishermen. Community empowerment aims to increase the productivity of the target group after being affected by the COVID-19 pandemic. The lives of the Balinese people, who mostly rely on the tourism sector, are in a very bad state which has an impact on all workers in the tourism sector and their families which affect the overall economic growth. The abundant fishery products are usually intended for restaurants and hotels in the form of fresh fish or seaweed. In a pandemic situation, the abundance of marine products cannot be marketed. The output of the activity is expected to increase the productivity of the fishing community after the pandemic, so that sustainable tourism development efforts can be realized. Keywords: community empowerment, fishing groups, the COVID-19 pandemic.